Doar Ex. 6 va rog.
--------------------------
Anexe:
Răspunsuri la întrebare
Răspuns de
1
a. p : 2x - 6 -3x + 6 = -x
- x = 5x + 1 , x∈R ; -x -5x = 1 ; -6x = 1 ; x = - 1 /6 A
b. p: x /2 + x/ 6 = ( 3x + x) / 6 = 4x /6 = 2x / 3
2x/ 3 = 1/8 - x/ 3
2x/3 + x /3 = 1/ 8 ; 3x/3 = 1/ 8 ; x =1/8 ; x∈ R A
c. p: I x -3I = 7
x -3 = 7 x -3 = - 7
x = 7 +3 =10 x = -7 +3 = - 4 A
d. x² - 4x + 4 +2x = x² + 2x +1
-2x + 4 = 2x + 1
- 2x - 2x = 1 - 4
- 4x = - 3 ; x = - 3 / ( - 4 ) = 3 /4 ∉ Z F
- x = 5x + 1 , x∈R ; -x -5x = 1 ; -6x = 1 ; x = - 1 /6 A
b. p: x /2 + x/ 6 = ( 3x + x) / 6 = 4x /6 = 2x / 3
2x/ 3 = 1/8 - x/ 3
2x/3 + x /3 = 1/ 8 ; 3x/3 = 1/ 8 ; x =1/8 ; x∈ R A
c. p: I x -3I = 7
x -3 = 7 x -3 = - 7
x = 7 +3 =10 x = -7 +3 = - 4 A
d. x² - 4x + 4 +2x = x² + 2x +1
-2x + 4 = 2x + 1
- 2x - 2x = 1 - 4
- 4x = - 3 ; x = - 3 / ( - 4 ) = 3 /4 ∉ Z F
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă